Etherospermia: The sky-seeding project - Michaloudis, Ioannis; Aleksandrow, Luke (64th International Astronautical Congress, 2013)
This paper presents the artistic practice of the researcher Ioannis Michaloudis with a space technology material and its potential use for cultural utilization of space. Since 2001 his Art&Science research projects have been based on the space technology nanomaterial silica aerogel, which Michalou(di)s considers a personification of our wounded sky. For humanity, the step towards space is a real “bridge moment” analogue to when organisms evolved and moved out, from water to earth. For this space era, humans need to develop new organs and new skills. Otherwise they need to cultivate new skies, in response to the breaking of our atmosphere’s dome. Etherospermia (εθεροσπέρμια) is an invented word from ether and panspermia. The Etherospermia project is targeting to the creation of new atmospheres on other planets. Imagine an astronaut who, during his space walk, will seed fragments of Michalous’ silica aerogel Skies into space; as if these sky-spores could grow into new atmospheres on other planets and thus make them habitable. This paper will develop the general public outputs of this idea by presenting seven artworks: Michalous’ A Portable Sunset, A piece of sky in between your fingers, My first time I touch a cloud, Bottled Sky, (M)other Earth, (L)imited sky and Aleksandrow’s Broken Silence.